Die sowjetischen Geheimdienste in der SBZ/DDR von 1945 bis 1953 - Foitzik, Jan (Texte und Materialien zur Zeitgeschichte, 2009)
After 1945, the Soviet secret services made a significant contribution to the formation of the GDR along Soviet lines. Mass arrests and purges accompanied the activities of the military branches of the NKVD-MVD and MGB. This source work, opening with a well-researched introduction to the historical context, is the first in the German language to examine the role of the Soviet secret police in the Soviet occupied zone and subsequently the GDR. Documented are the NKVD-MGB's formation, field of activity and daily routines.